2013
DOI: 10.1016/j.cviu.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic angle selection in binary tomography

Abstract: a b s t r a c tIn this paper, we present an algorithm for the dynamic selection of projection angles in binary tomography. Based on the information present in projections that have already been measured, a new projection angle is computed, which aims to maximize the information gained by adding this projection to the set of measurements. The optimization model used for angle selection is based on a characterization of solutions of the binary reconstruction problem, and a related definition of information gain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In [28] it was shown that, for |S| = 4, the unique situations where F S has some coefficient outside {−1, 0, 1} correspond, precisely, to the choices 4 } in the first case, and S 1 = {u 1 , u 2 }, S 2 = {u 3 , u 4 } in the second case. Also, we define the set S 1 − S 2 as follows…”
Section: Previous Results Employedmentioning
confidence: 99%
See 4 more Smart Citations
“…In [28] it was shown that, for |S| = 4, the unique situations where F S has some coefficient outside {−1, 0, 1} correspond, precisely, to the choices 4 } in the first case, and S 1 = {u 1 , u 2 }, S 2 = {u 3 , u 4 } in the second case. Also, we define the set S 1 − S 2 as follows…”
Section: Previous Results Employedmentioning
confidence: 99%
“…The related digital image is shown in Figure 3 A complete reduction of P (x, y) is obtained just by three choices, corresponding to the selected pairs (1, 2), (2, 1), and (1, 0). This provides the following reduction Therefore, the points (2, 2), (3,3), and (4, 4), having multiplicity 4, are covered 3 times, the points (4, 3), (3,4), (3,2), and (2, 3), having multiplicity 3, are covered 3 or 2 times, and all the double points are covered 1 or 2 times. Consequently (H(x, y) + xy 2 + x 2 y + x)F S (x, y) represents the corresponding reduced polynomial.…”
Section: Examplementioning
confidence: 99%
See 3 more Smart Citations